General issues in impact assessment - Lipner, M.E.; Swallow, B.M. (International Livestock Centre for Africa, 1992)
This introductory paper raises general issues and poses questions that are pursued in the other papers. The initial premise of this paper is that impact cannot be discussed in isolation from the broader context of research and development and the overall priorities guiding the centres research, training, and networking activities. ILCA's outputs, the research process, criteria for evaluating impacts are discussed supported by four case studies namely: ILCA's research on tenure policy and alley farming, forage legume research in the subhumid zone of West Africa with ILCA's systems research methodology, organisational impacts through ILCA's research networks, and pricing policies in sub-Saharan Africa.